Phyto, Physicochemical Standardization and TLC fingerprinting of Medicinal Plant Couroupita guianensis - Raja S; Ravindranadh K (International Journal of Phytomedicine, 2014)
The aim of the study is to cover the pharmacognostical and preliminary phytochemical screening of Couroupita guianensis. Couroupita guianensis belonging to the family Lecythidaceae, a widely grown plant throughout India. The plant has many valuable medicinal properties. The plant was collected from the local regions and was authenticated by the botanist. Pharmacognostical study included macroscopical characters, microscopical characters, physico-chemical constants and fluorescence analysis. Preliminary phytochemical screening includes phytochemical extraction, phytochemical testing and thin layer chromatography (TLC). While performing the successive solvent extraction, the maximum extractive value of 8.2% was seen in methanol extract. Preliminary phytochemical studies show the presence of carbohydrates, flavonoids, alkaloids, tannins, proteins and amino acids. Performing TLC of chloroform and ethyl acetate extracts using different solvent system, alkaloids, steroids, and flavonoids were identified. The study helps in the correct identification of the herb. The presence of alkaloids, steroids and flavonoids explains that the plant must have valuable medicinal properties which must be explored.